ANALISIS YURIDIS TERHADAP PERATURAN JAKSA AGUNG NOMOR PER-014/A/JA/11/2012 TENTANG KODE PERILAKU JAKSA: HARMONISASI ANTARA PERATURAN JAKSA AGUNG DAN PRINSIP ETIKA HUKUM (Kajian Etika Profesi Hukum) - Mohammad Sirodjat Tamimi; Amanulloh Amanulloh; Muhamad Soli (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Regulation of the Attorney General No. PER-014/A/JA/11/2012 on the Code of Conduct for Prosecutors is an important regulation governing ethical and behavioral guidelines for prosecutors in carrying out their duties and functions. In the juridical analysis of this regulation, the main focus lies on the harmonization between the provisions set out in the regulation and the broader principles of legal ethics. The principles of legal ethics that apply in the justice system prioritize justice, objectivity, transparency and accountability. Therefore, it is important to assess whether the Prosecutor's Code of Conduct is in line with the values of legal ethics, as well as how its implementation can affect the quality of law enforcement and the integrity of the prosecutorial institution. The analysis also identifies the challenges faced in implementing the code of conduct, including in the aspects of supervision and enforcement of discipline against prosecutors who violate the code of conduct. Thus, this study aims to provide insights into the compatibility between the Attorney General's Regulation and legal ethical principles and provide recommendations regarding improvements that can be made to strengthen the integrity and professionalism of prosecutors in the Indonesian justice system.